ANALISIS BEBERAPA FAKTOR YANG BERPENGARUH TERHADAP VOLUME EKSPOR KOPI PROVINSI BALI PERIODE 1990 - 2006 - Adwitya Sanjaya, Putu Krisna (INPUT Jurnal Ekonomi dan Sosial; Vol. 1, No. 2 Agustus 2008)
Foreign trading, especially export, has an important in? uence for many countries including Indonesia. Indonesian’s export is very diverse, includes migas & non-migas. Export non-migas , which is one of Indonesian’s main exports, includes the horticulture sector. Indonesian’s foreign trading operations will obviously have an impact on the development of the regional trading segments,without an exception for Bali Province. Coffee is becoming one of the commodity exports in Bali Province. This study is intended to ? nd out how price, American Dollar’s rates and the coffee export’s policy simultaneously and partially in? uenced the coffee export’s volume of Bali Province during 1990-2006. The time series data of export’s volume, average price of coffee export, and American Dollar’s rates are stationery at second difference. After performing analysis of the in? uenced of average price of coffee export, American Dollar’s rates and the coffee export’s policy on the coffee export’s volume of Bali Province during 1990-2006, we can conclude that average price of coffee export, American Dollar’s rates and the coffee export’s policy simultaneously have signi? cant in? uences on the coffee export’s volume of Bali Province during 1990-2006. Price and American Dollar’s rates are not partially signi? cant on in? uencing the coffee export’s volume of Bali Province during 1990-2006. Meanwhile, after the implementation of the coffee export’s policy, Bali’s coffee export’s volume is experiencing a decrease in the amount of exports compare to before the introduction of the export’s policy. The dominant variable that most in? uenced the coffee export’s volume of Bali Province during 1990-2006 is the American Dollar’s rates, because American Dollar’s rates have the highest absolute value of standardized coef? cients beta.
Keywords: Price, Interest,and Export Coffee Policy